Pemanfaatan Pemasaran Digital untuk Meningkatkan Pemasaran dan Penjualan Kain Batik Desa Klampar Pamekasan - Oktaviana, Ika; Dewi Pusparini; Imam Wahyudi; Nanang Setiawan (MITRA: Jurnal Pemberdayaan Masyarakat, 2024)
This socialization and mentoring activity was carried out as a form of community service to increase the income of batik craftsmen in Klampar Village during the pandemic. The main objective of this activity is to provide knowledge transfer and practices related to the use of markets in marketing batik products. This is very important considering that most batik sales in Klampar Village still use traditional methods, coupled with the impact of the COVID-19 pandemic which requires craftsmen to avoid crowds. This community service activity was carried out through several stages, namely: supervision, preparation, implementation, evaluation, and preparation of reports. The results achieved showed a significant change in sales methods, with 93% of participants who previously made face-to-face sales in traditional markets, now switching to digital online marketing without having to meet buyers directly. In addition, 90% of participants succeeded in creating social media and marketplace accounts to market their products. Based on these results, it can be concluded that batik craftsmen feel great benefits from this community service program, because the use of digital marketing has proven to be easy, effective, and efficient and has an impact on increasing batik sales income.